Trophic preference and preliminary indication of phylloplane fungal influence on the diet of the non-native Gammarus roeselii Gervais 1835 (Amphipoda, Gammaridae) in the sub-lacustrine Ticino river basin (Lombardy, Northern Italy) - Daniele Paganelli; Andrea Gazzola; Marinella Rodolfi; Renato Sconfietti; Anna Maria Picco (Italian Journal of Mycology, 2017)
Gammarids are one of the most successful invaders in freshwater ecosystems due to both their diet plasticity and high reproductive capacity. One such amphipod, Gammarus roeselii, has recently colonised the southern part of the sub-lacustrine Ticino River basin (Northern Italy), where its ecological niche overlaps with the native species Echinogammarus stammeri. In the present paper the food preferences of G. roeselii have been investigated, testing the palatability of different food sources: three macrophytes and three different leaf debris. Moreover, an explorative mycological analysis on the three different leaf debris used in the experiment has been performed. Results of the short-term experiment suggest that aquatic plants are less palatable than allocthonous detritus, probably because they can contain secondary metabolites (i.e. tannins) and they have lower nutrient tissues with very high water content. On the contrary, G. roeselii showed a clear preference for the oak leaves, resulted colonized by a more abundant fungal biomass and, therefore, more palatable too.